PENGARUH ASIMETRI INFORMASI, PENEKANAN ANGGARAN, KOMITMEN ORGANISASI DAN LOCUS OF CONTROL TERHADAP HUBUNGAN PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN (STUDI EMPIRIS PADA SATUAN KERJA PERANGKAT DAERAH KOTA SAWAHLUNTO) - Mai Elva Sundari; Emrinaldi Nur DP; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Budgetary participation is the process of budgeting that involves many stakeholders for budget achievement. During this process, it’s possible for them to perform budgetary slack and effect on budget goal. The purpose of this research is to explore the influence of information asymmetry, budget emphasis, organizational commitment and locus of control to the relationship of budgetary participation to budgetary slack. The population in this research is 22 office in local government (SKPD) of Sawahlunto city. The sampling design of this research is purposive sampling with the final sample is 91 people as a three till four echelon of 6 local government (SKPD) that detected perform the budgetary slack, they are: department education and youth sport, department of civil registration, food crops and holticulture service, public works service, investment office and archives and library area office. This research used primary data dissemination of the questionnaire conducted 6 office local government (SKPD) in Sawahlunto city. Technical analysis for test is simple linear regression and MRA. The results of this research showed that budgetary participation significant influence to budgetary slack. Information asymmetry, budget emphasis, organizational commitment and locus of control significant influence in relationship budgetary participation to budgetary slack.Keywords: Budgetary Participation, Information Asymmetry, Budget Emphasis, Organizational Commitment, Locus of Control, Budgetary Slack.